Secondary Hemophagocytic Syndrome: The Importance of Clinical Suspicion. (18th May 2014) - Oliveira, Cristina; Chacim, Sérgio; Ferreira, Isabel; Domingues, Nelson; Mariz, José Mário
Abstract : Hemophagocytic syndrome is a rare and potentially fatal disorder characterized by pathological immune activation associated with a primary familial disorder, genetic mutations, or occurring as a sporadic condition. The latter can be secondary to infections, malignancies, or autoimmune diseases. Clinically, patients present signs of severe inflammation, with unremitting fever, cytopenias, spleen enlargement, phagocytosis of bone marrow elements, hypertriglyceridemia, and hypofibrinogenemia. Increased suspicion is determinant to timely initiate treatment in an attempt to alter the natural history. The authors present three clinical cases of this syndrome, with a brief review of the diagnostic criteria and treatment.